Changing paradigm in learning in the field of Neurosciences during COVID-19. - Shrestha, Resha (Nepal Journal of Neuroscience, 2022)
Although the number of COVID-19 cases are decreasing in recent days and a sense of normality can be felt, the situation was completely different for a couple of years. Like most of the fields, learning in the field of neurosciences was also heavily impacted due to COVID-19. Multiple ways of learning gained popularity during the pandemic which has changed the way neuroscience is taught and learnt these days.